Salmonella spp. in liver processing in a pig slaughterhouse in the south of Brazil (Research, Society and Development, 2021)
The objective of the work was to evaluate the presence of Salmonella spp. during the slaughter and processing of swine giblets (Pork Liver) in a slaughterhouse in Rio Grande do Sul, identifying which stages have the highest occurrence of contamination. The research was carried out in a pig slaughterhouse in the state of Rio Grande do Sul. The collections were carried out on the surfaces of the carcasses, utensils, equipment, tables and gloves of the handlers during the slaughter process and collection of the final product. In the study carried out of a total of 72 samples from the analyzed carcasses, 18 presented the presence of Salmonella spp., Resulting in a frequency of 25% of samples with the presence of the bacterium and 75% with the absence of Salmonella spp. The results presented may be related to contamination of the raw material or cross contamination during the process, which occur in the slaughterhouse along the slaughter line. It is determined that the critical stages with prevalence of Salmonella spp. are the bleeding, before the scalding tank and in the evisceration. Scalding and buckling proved to be effective operations in reducing the bacteria in the carcasses. The level of contamination after evisceration is at risk of cross contamination. It is essential to hygienic sanitary care in the processing steps, maximizing the microbiological quality of the final product.